Advances on the Clinical Application of Stent Placement for Colorectal Cancers (CRCs) (Journal of Fiber Bioengineering and Informatics, 2018)
Colorectal stents have been reported as an effective alternative to surgery for the palliation or as a “bridge to surgery” for patients with obstructing colorectal cancers. This review describes the need for colorectal stent placement, distinction from colostomy and resection with primary anastomosis, the requirements for placement, and the many efforts over the past century to accomplish this goal experimentally and clinically. This work briefly presents both commercially available stents and relevant newly developed stents with experimental bio-functional materials, including elastic polymers (polyurethane), the biodegradable and bioresorbable materials, and the naturally occurring materials, focusing on their potential applications in the development of future colorectal substitutes. This paper also examines the critical issues and scientific challenges that require further research and cooperation of multidisciplinary teams.